Palm Oil in Gelato for Better Melting and Mouthfeel Properties - Eddy Kemenady; Muhammad Eka Pramudita; Muhammad Arief Prabawa (Indonesian Oil Palm Society /IOPS (Masyarakat Perkelapa-sawitan Indonesia /MAKSI), 2019)
Recently, the growth of gelato outlets in Bali, Surabaya, Jakarta, and many cities in Indonesia hit 30-45% since 2013 to 2018. The gelato outlet has good margin at least 50% gross profit. However, the consumers need gelato not only good in taste but also it is not easy to melt. In modern world the formulations are based on premix of modified starch, sugar, emulsifier, stabilizers and milk solid nonfat. One of most popular brands of gelato premix is imported from Italy. In recent years, the use of palm oil in gelato is hardly reviewed. However, in ice cream business, palm oil is used widely. The fat blends of palm oil and palm kernel oil at PO/PKO (30/70; w w-1) was used, because the solid fat content (SFC) properties is similar to the SFC of butter oil. The level of this fat blend in gelato was varied from 5, 8, 10 and 12%. This research showed that the optimum fat blend addition in formula was found at 8%. The dripped test is used at 28 °C ambient temperature to measure heat stability. It was found that the more fat blend in gelato, the more stable the texture to heat shock and made the gelato easy to scoop as well. The cost in formulation with this 8% palm oil blend to gelato formulation is only 2.8%. Therefore, the palm oil blend in gelato formulation gives significant improvement melting and mouthfeel properties at insignificant cost addition.